Desain Formulir Rekam Medis Di Bagian Pendaftaran Pada Kegiatan Khitanan Masal Al-Khitan Madinah Banjarmasin - Estiyana, Ermas; Yunita, Nirma (Akademi Perekam dan Informasi Kesehatan Imelda, 2023)
In all health services it is mandatory to provide recording services medical records, as for the benefits of medical records, one of which is useful as written evidence of acts of service to a patient, too able to protect the legal interests of the patient concerned, hospitals and doctors and other health workers. Medical record is a file that contains notes and documents regarding patient identity, examination, treatment, actions, and services that have been given to patients. Al-Khitan Banjarmasin, which has been established since 2016, in every implementation of mass circumcision does not have a medical record form. The purpose of this study was to make a medical record form in the registration section of the Al-Khitan Medina Banjarmasin mass circumcision. This research method is a qualitative descriptive research. The subjects in this study consisted of the main informants who were registration officers of Al-Khitan Medina Banjarmasin, triangulation informants who were in charge of Al-Khitan Medina Banjarmasin, using observation and interview guide instruments. The data analysis technique is descriptive qualitative. The results of this study are the design of medical record forms that are made by taking into account the anatomical aspects, physical aspects and content aspects. The anatomical aspects of this design include the title of the form, the name of the circumcision house, Al-Khitan, Medina, Banjarmasin, the address of the circumcision house, no. medical record, introduction, basic information explaining the purpose of using the form in question, instructions containing clear instructions for fillers to write down patient data later. Physical aspects are made according to using black ink, white paper color, HVS paper material, A4 paper size, Aspects of the contents of the form are designed consisting of number, date of visit, history of illness, action, therapy/medicine, name and initials of the officer.